The Predictive Power of Capital Asset Pricing Model and Consumption Capital Asset Pricing Model in Nigeria - Aderounmu, Busayo; Oni, Olubusayo (Center of Research and Innovation Strengthen LP2M UNM, 2024)
The examination of the predictive power of CAPM and CCAPM in determining risk premium in Nigeria between 1999-2014 shows that CAPM is statistically significant for all equities although the coefficient is relatively high. However, CCAPM was statistically not significant for all equities listed though the results was meaningful. This is in line with the findings of Mankiw and Shapiro (1986), Chen (2003) and Idolor (2012) where the authors’ findings did not support CCAPM but concluded that the superiority of CAPM is a puzzle. In conclusion Capital Asset Pricing Model produced a more meaningful and statistically significant result in predicting equity premium in Nigeria than Consumption Capital Asset Pricing Model.